Cultural adaptation and value-semantic content of the socialization process - МорщаковаО. C.; Буда, Т. Й. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
Reveals the possibility of cultural adaptation, described the process of socialization as a process of value-semantic formation and self-assertion of the individual in a situation of transformational changes of modern social relations full of contradictions, new opportunities and prospects.